MR Evaluation of Hydrocephalus - El Gammal, Taher; Allen, Marshall B.; Brooks, Betty Sue; Mark, Edward K. (American Journal of Neuroradiology, 1987)
An analysis of sagittal T1-weighted MR studies was performed in 23 patients with hydrocephalus, 58 patients with atrophy, and 100 normal patients. The average millopontine distance was 1.15 cm for the normal group, 1.2 cm for patients with atrophy, and 7.5 mm for patients with hydrocephalus. A reduction of the mamillopontine distance below 1.0 cm was found in 22 patients with hydrocephalus, 5 patients with atrophy, and 15 normal patients. Dilatation of the anterior third ventricle was noted in 21 patients in the hydrocephalus group and in none of the patients in the atrophy and normal groups. The average thickness of the corpus callosum at the level of the foramen of Monro was 6 mm in normal subjects and was reduced below 6 mm in 16 of the hydrocephalus patients. Smooth elevation of the corpus callosum was noted in 20 hydrocephalus patients, in 2 patients with atrophy, and in none of the normal patients. MR improves the accuracy of diagnosis in patients with hydrocephalus both because of its ability to show small obstructing lesions that are not depicted by CT and because the mass effect of the distended supratentorial ventricles produces anatomic changes that are delineated with precision by MR.